Isolation of major alkaloids from Mitragyna Speciosa (Kratom) / Mohd Firdaus Ahmad Akhibi - Ahmad Akhibi, Mohd Firdaus (Faculty of Applied Sciences, 2008)
Mitragyna speciosa (Rubiaece) is a tropical plant indigenous to Thailand and Malaysia. The leaves of this plant, known as “Kratom” in Thailand and “Biak-Biak” in Malaysia, were traditionally used by many laborers as a stimulant like coca or as a substitute for opium. But the use of this plant is now illegal in these countries because of its narcotism. The unique properties of this medicinal plant have attracted many researchers over the last fifty years. An alkaloidal extract was prepared from the leaves of Mitragyna speciosa with chloroform. After extraction, the major alkaloid was isolated by using chromatographic technique such as column chromatography. Purification process was carried out by using Preparative Thin Layer Chromatography. The structure of pure alkaloid was elucidated by using various spectroscopic methods including NMR, GCMS, FTIR and UV. From the research, the structure of major alkaloid cannot be seen. This is because a lot of impurities in the samples preparation even though the purification technique had been used. As a conclusion, an alkaloid was successfully isolated. Base on the comparison of proton NMR result and that of in the Literature Review found that they are not the same alkaloid. However, the structure of the alkaloid cannot be elucidated due to the presence of other contaminants in an alkaloid sample.